Time-dependent axonal impairment in experimental model of brain oedema - Kozler, Petr; Riljak, Vladimír; Pokorny, Jaroslav (Neuro endocrinology letters, 2010)
OBJECTIVES: Clinically very serious condition of ischaemia and brain injury which are often associated with brain oedema is frequently accompanied by the impairment of the structural integrity of axons. We wondered whether the brain oedema (without ischemia brain injury) can induce structural axonal impairment. METHODS: Brain oedema was induced by osmotic blood-brain barrier opening with 20% mannitol applied selectively into the internal carotid. Axonal changes were recognized as signs of myelin disintegration (oedematous vesicles, varicosity, myelin fragmentation) at histological sections stained with Black Gold in hippocampal areas CA1 and CA3 and in the dentate gyrus and cerebral cortex at time intervals of one hour, one day, three days and one week after the oedema induction. RESULTS: Impairment of the structural integrity was identified in myelin sheets in all areas studied in all experimental groups. Whereas in the control group axon were of the uniform diameter, in the experimental groups various forms of myelin disintegration were observed. The progression of myelin damage depended on the time elapsed after the oedema induction. CONCLUSION: Opening the blood-brain barrier with an osmotic insult induces brain oedema which represents a factor triggering axonal impairment accompanied with myelin changes. The development of axonal changes initiated by brain oedema only (without ischemia brain injury) is a novel observation.
Keywords: edém mozku; Dentate Gyrus; Myelin Sheath; hematoencefalická bariéra; axony; Blood-Brain Barrier; Female; analýza rozptylu; gyrus dentatus; Analysis of Variance; krysa rodu Rattus; Brain Edema; zvířata; potkani Wistar; časové faktory; mannitol; ženské pohlaví; Rats, Wistar; Male; Mannitol; Rats; Axons; Animals; mužské pohlaví; Time Factors; myelinová pochva